2017
DOI: 10.1002/brb3.711
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA expression in peripheral blood mononuclear cells and suicide risk in Chinese patients with major depressive disorder

Abstract: Background WHO stated that nearly one million people commit suicide every year worldly, and 40% of the suicide completer suffered from depression. The primary aim of this study was to explore the association between long noncoding RNAs (lncRNAs) expression in peripheral blood mononuclear cells (PBMCs) and suicide risk of patients with major depressive disorder (MDD).MethodsUsing Human LncRNA 3.0 microarray profiling which includes 30,586 human lncRNAs and RT‐PCR, six down‐regulated lncRNAs were identified diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Moreover, PSORS1C3 is a known psoriasis susceptibility gene further supporting a role in immune system regulation [34]. Futhermore, a recent study identified six lncRNAs (see Table 2) whose expression was downregulated in peripheral blood samples of MDD patients with SI [99] . Finally, Punzi et al showed that the expression of an uncharacterized lncRNA, LOC285758, is significantly increased in violent suicide cases compared to non-violent suicide cases [100].…”
Section: Non-coding Rnas and Their Role In Sbmentioning
confidence: 94%
“…Moreover, PSORS1C3 is a known psoriasis susceptibility gene further supporting a role in immune system regulation [34]. Futhermore, a recent study identified six lncRNAs (see Table 2) whose expression was downregulated in peripheral blood samples of MDD patients with SI [99] . Finally, Punzi et al showed that the expression of an uncharacterized lncRNA, LOC285758, is significantly increased in violent suicide cases compared to non-violent suicide cases [100].…”
Section: Non-coding Rnas and Their Role In Sbmentioning
confidence: 94%
“…TEs represent important sources of epigenetic regulation (Mustafin, Khusnutdinova, 2017), thus providing their study as a promising direction for identifying the mechanisms of SB development. A differential expression of six lncRNAs (TCONS_00019174, ENST00000566208, NONHSAG045500, ENST00000517573, NONHSAT034045, and NONHSAT142707) was observed in peripheral blood leukocytes of patients with SB and MDD (Cui et al, 2017), while 23 different lncRNAs were differentially expressed in the brains of individuals with completed suicide (Zhou et al, 2018) compared to the control group. Protein-encoding genes localized distally from lncRNAs identified in these studies are involved in the organization of the cytoskeleton and plasmatic membrane, cell adhesion, DNA binding and regulation of dendrite development (Zhou et al, 2018).…”
Section: The Role Of Long Non-coding Rnasmentioning
confidence: 97%
“…These results promote further research of lncRNAs, which makes it possible to develop effective methods for SB prevention and therapy. Analysis of lncRNAs differentially expressed in SB (TCONS_00019174, ENST00000566208, NONHSAG045500, ENST00000517573, NONHSAT034045, and NONHSAT142707) has been proposed as a potential diagnostic and therapeutic SB biomarker for the prevention of suicidal attempts in MDD patients (Cui et al, 2017). The changes in miRNA expression identified in the brain of individuals with completed suicide can represent the basis for both clarifying SB pathogenesis and developing a targeted SB therapy (Maussion et al, 2012;Smalheiser et al, 2012;.…”
Section: Prospects For Epigenetic Studies Of Suicidal Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies showed that 6 lncRNAs (TCONS_00019174, ENST00000566208, NONHSAG045500, ENST00000517573, NONHSAT034045, and NONHSAT142707) had diagnostic value, therapeutic evaluation, differential diagnosis, and participated in many functions in the central nervous system [ 19 ]. The expression of 6 lncRNAs was significantly correlated with suicide risk [ 20 ]. This study aimed to investigate whether 3 candidate differentially expressed lncRNAs (NONHSAT142707, NONHSAG045500, ENST00000517573) in MDD, which have much higher expression in the brain, can internalize SERT and reduce SERT-binding sites through mediating SERT mRNA levels in SK-N-SH cells.…”
Section: Introductionmentioning
confidence: 99%